Modelagem de processos utilizando a teoria das restrições na divisão de transportes de uma universidade pública - Fernandes, Wanderson Carvalho (2018)
The moment experienced by the public administration reveals its multiple challenges, for the fact that it is the instrument by which the State responds with efficiency and effectiveness to new issues arising from the expansion of the role of the State as a service provider, from a greater requeriment by citizens, and from the increase of complexity of social demands. The way in which public management fulfills this role includes the assimilation of new tools and instruments for the diagnosis and solution of problems. From this perspective, this work approached in particular the transportation sector of a Federal Institution of Higher Education, by means of the formulation of a method, with a view to the modeling of processes and analysis of bottlenecks in the place. For this, i have used the process of reasoning from the Theory of Constraints. The enforcement of the method proposed in the Transport Division demonstrated its viability and practicality, as a tool for diagnosis and solution of problems, resulting in the formulation of an action plan to be proposed for the place, indicating the actions necessary to solve the identified bottlenecks .